The International School’s Culture in Indonesia and Brunei Darussalam - Muhammad Kristiawan; Suhono Suhono; Mohd Hilmy Baihaqy Yussof; Muslimah Muslimah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
An understanding of a school’s culture was essential to quality management. In this study the researchers identified the international school’s culture in Singapore International School (SIS) Palembang, Indonesia and Jerudong International School (JIS) Brunei Darussalam. The approach used in this paper was qualitative, case study. The data were collected by using observation, interview, and documentation. The data were analyzed by using Miles and Huberman’s Model. The results obtained indicate that the school’s culture in SIS was building students’ character such as honesty, sincerity, creativity, compliance with rules and norms. While in JIS, the students should take responsibility for themselves and others. They take the initiative, evaluate the situation in front of them and make decisions accordingly. JIS thrives on mutual respect by working with people from different backgrounds. Keywords: School’s Culture, SIS Palembang, JIS Brunei Darussalam